Dukungan Keluarga pada Kekambuhan Penyalahguna Narkotika - Hapsari, Filia Linda; Induniasih, Induniasih (Media Ilmu Kesehatan, 2012)
Background : Drug abuse is one of the cause death, there is 15.000 every year.Report of BNK Yogyakarta the case of drug abuse are 12.848 students of elementaryschool; 110.870 of junior high school and senior high school students. Relapse is one ofthe effect drug of abuse that cause addiction for both acute/ cronic disease. The factorthat influence of relapse is family support. Family support can make relapse decreasing.Objective : This study aimed to determine the relationship between family support andrelapse of drug abuser in the Social Institution Pamardi Putra Purwomartani KalasanSleman Yogyakarta.Method : The study was kuatitative non eksperimental with observasional cross sectionaldesign. Population of drug abuse that lead rehabitation in Social Institution Pamardi PutraPurwomartani were 24 people. The analysis technique used Spearman Rank to see thevariables relation and correlation coefficient test would use to find out the strenght ofrelation. The research was conducted in Social Institution Pamardi Putra Purwomartani onJuly 18th, 2011.Result : on this study, there were 24 respondents. The respondent who had moderatefamily support was 50% with high relapsing 54,2%. There was any relation betweenfamilysuport and relapse of drug abuser, with significant value 0,802. That indicatestrenght relation.Conclusion : There is any relation between family support and relapse of drug abuser inSocial Institution Pamardi Putra Purwomartani Kalasan Sleman Yogyakarta. Key word : family support, relapse, drug abuser